Fibular Strut Graft Augmentation for Open Reduction and Internal Fixation of Proximal Humerus Fractures: A Systematic Review and the Authors' Preferred Surgical Technique. Issue 7 (21st July 2016) - Saltzman, Bryan M.; Erickson, Brandon J.; Harris, Joshua D.; Gupta, Anil K.; Mighell, Mark; Romeo, Anthony A.
Background: Proximal humerus fractures are common problems plaguing the elderly population. Purpose: The purposes of this study were to determine the outcomes of fibular strut allografts in treatment of proximal humerus fractures with open reduction internal fixation (ORIF) and to present the authors' preferred surgical technique. The hypothesis was that the use of fibular strut allografts in treating proximal humerus fractures with ORIF will provide low reoperation rates with acceptable outcomes. Study Design: Systematic review; Level of evidence, 4. Methods: A systematic review was registered with PROSPERO and performed with PRISMA (Preferred Reporting Items for Systematic reviews and Meta-Analyses) guidelines using 3 publicly available free databases. Therapeutic clinical outcome investigations reporting arthroscopic elbow outcomes with levels of evidence 1 through 4 were eligible for inclusion. All study, subject, and surgical technique demographics were analyzed and compared between continents and countries. Statistics were calculated using Student t tests, 1-way analysis of variance, chi-square tests, and 2-proportion Z tests. Results: Four studies met the inclusion criteria. While there is great heterogeneity existing in the literature surrounding use of a fibular strut allograft as an adjunct to ORIF of proximal humerus fractures, current evidence shows a humeral head screw penetration rate of 3.7% with acceptable functional outcome scores, with a reoperation rate of 4.4% at a weighted mean 80.78 weeks (1.55 years) of postoperative follow-up. Conclusion: There is great heterogeneity that exists in the literature surrounding the use of a fibular strut allograft as an adjunct to ORIF of proximal humerus fractures. Current evidence shows a screw penetration rate of 3.7% with acceptable functional outcome scores, demonstrating fibular strut allograft is a viable option for treating proximal humerus fractures.